Serological Assessment of 18 Pathogens and Risk of AIDS-Associated Non-Hodgkin Lymphoma. (1st March 2019) - Halec, Gordana; Waterboer, Tim; Brenner, Nicole; Butt, Julia; Hardy, W. David; D'Souza, Gypsyamber; Wolinsky, Steven; Macatangay, Bernard J.; Pawlita, Michael; Detels, Roger; Martínez-Maza, Otoniel; Hussain, Shehnaz K.
Abstract : Background: HIV infection is associated with increased susceptibility to common pathogens, which may trigger chronic antigenic stimulation and hyperactivation of B cells, events known to precede the development of AIDS-associated non-Hodgkin lymphoma (AIDS-NHL). Methods: To explore whether cumulative exposure to infectious agents contributes to AIDS-NHL risk, we tested sera from 199 AIDS-NHL patients (pre-NHL, average lead time 3.9 years) and 199 matched HIV-infected controls from the Multicenter AIDS Cohort Study, for anti-IgG responses to 18 pathogens using multiplex serology. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using conditional logistic regression models. Results: We found no association between cumulative exposure to infectious agents and AIDS-NHL risk (OR 1.01, 95% CI: 0.91 to 1.12). However, seropositivity for trichodysplasia spinulosa polyomavirus (TSPyV), defined as presence of antibodies to TSPyV capsid protein VP1, was significantly associated with a 1.6-fold increase in AIDS-NHL risk (OR 1.62, 95% CI: 1.02 to 2.57). High Epstein–Barr virus (EBV) anti-VCA p18 antibody levels closer to the time of AIDS-NHL diagnosis (<4 years) were associated with a 2.6-fold increase in AIDS-NHL risk (OR 2.59, 95% CI: 1.17 to 5.74). In addition, high EBV anti-EBNA-1 and anti-ZEBRA antibody levels were associated with 2.1-fold (OR 0.47, 95% CI: 0.26 to 0.85) and 1.6-fold (OR 0.57, 95% CI: 0.35 to 0.93) decreased risk of AIDS-NHL, respectively. Conclusions: Our results do not support the hypothesis that cumulative exposure to infectious agents contributes to AIDS-NHL development. However, the observed associations with respect to TSPyV seropositivity and EBV antigen antibody levels offer additional insights into the pathogenesis of AIDS-NHL. Abstract : Supplemental Digital Content is Available in the Text.